Mission planning and scheduling for Earth observation space system. (20th February 2020) - Qamar, Amr; Salah, Essam Eldin; Badran, Khaled M.; ElNashar, Gamal A.
Planning and scheduling systems are needed to manage Earth observing satellites for satisfying the optimum usage of the constellation's resources. This is a combinatorial optimisation NP-hard problem which is solved in this paper using the constraint programming technique. The proposed system can deal with a heterogeneous constellation that consists of satellites with different manoeuvrability, placed in different orbits, and loaded with different payloads. The system's user can choose one of six optimisation objectives, three of them were not used before, for constructing the satellites' mission plan. Searching within the system is performed using one of five different search algorithms. The system produces plans with different planning horizons ranging from one track to more than one month. The obtained results depict that the proposed system behaves, comparatively, in a perfect manner even when dealing with a complicated case study consisting of three satellites, 2, 500 targets, and one month planning horizon.